Проблеми інноваційного розвитку регіону - Прохоровська, С. А.; Дяків, О. П. (Видавництво Львівської політехніки, 2015)
Розкрито роль інновацій як чинника соціально-економічного розвитку регіону, охарактеризовано передумови активізації інноваційної діяльності на прикладі Тернопільської області; визначено основні завдання формування регіональної інноваційної системи та її складові; з’ясовано чинники інноваційної активності найманих працівників; обґрунтовано основні напрямки інноваційної діяльності в Тернопільській області і запропоновано шляхи їхньої реалізації. The role of innovations as a factor of socio-economic development of region is exposed in the article; the pre-conditions of activation of innovative activity are described on the example of the Ternopil area. It is grounded that fundamental scientific research-and-developments and inputs and use of innovative goods are the basis of innovative activity. The necessity of development of innovative politics in a region, that must be aimed at development of scientific research-and-developments, increase of production and realization of scientific products, solution of social problems of use the newest technologies, is well-proven. It is set that is creation of infrastructure of innovative activity is the major task at forming the regional innovative system in region. It is well-proven that fundamental scientific research-and-developments, creation of the system of support and advancement of innovations would be the basic ways of activation of innovative activity in a region. It is set that the effective bringing in of scientific and technical potential to the innovative projects is the important factor of the economy growing and increase of competitiveness of industries of economy. The basic tasks of forming of the regional innovative system and its constituents are certained: productive-technological, consulting, financial, skilled, informative and sale. The problems of innovative development in Ukraine and the region are investigated. Factors that influence on innovative activity of the hired workers are distinguished by priority: professional training and competence, creative capabilities, character of man, requirement in self-realization and self-perfection, requirement in material welfare, entrepreneurship. The influence of self-education, studies to the new professions and increase of level of qualification of workers on innovative development of the Ternopil area is found out. It is well-proven that creation economically of effective workplaces, that will allow to develop creative potential of the hired worker, promote the level of his qualification is the important direction of increase of innovative activity of region.
Problems of innovative development in the region
Keywords: інновації; інноваційний розвиток; ініціативність у праці; економічно ефективні робочі місця; регіон; чинники інноваційної активності; наймані працівники; навчання; innovations; innovative development; initiativeness in labour; economically effective workplaces; region; factors of innovative activity; hired workers; continuous